Percutaneous unilateral biportal endoscopy versus uniportal endoscopy for lumbar spinal stenosis: a single-centre, prospective, non-randomised cohort trial protocol - Xiang Li; Yong Yang; Lingjia Yu; Haining Tan; Yuquan Liu; Guangpeng Li; Yuanshun Lo; Zhu Bin (BMJ Open)
Introduction Unilateral biportal endoscopic (UBE) technique and uniportal endoscopic (UE) technique have both been used to treat lumbar spinal stenosis (LSS) with satisfactory outcomes. Although previous studies have reported no difference in clinical outcomes between UBE and UE techniques, the evidence was weak due to the lack of a prospective design. Therefore, the present prospective study aimed to compare the efficacy and safety of UBE and UE for treating patients with LSS.Methods and analysis This single-centre, prospective, non-randomised cohort trial is designed to compare the efficacy and safety of UBE and UE in treating patients with LSS. We will include 120 participants (60 per group) with single-level or double-level LSS. The primary outcome will be determined using the Oswestry Disability Index at the 12-month postoperative follow-up between the two groups. Secondary outcomes will include the following: visual analogue scale scores for lower back and leg pain, Japanese Orthopaedic Association score, modified MacNab criteria, Medical Outcomes Study 36-Item Short Form Health Survey, operation time, blood loss and duration of postoperative hospital stay. Radiographic outcomes will include the enlargement ratio of the dural sac, bony decompression range and preservation rate of the facet joint measured on postoperative radiological data. Laboratory outcomes will include postoperative creatine kinase level and erythrocyte sedimentation rate. Adverse events will be recorded to assess safety. Participants will be assessed by a blinded assessor preoperatively and postoperatively at 3 days, 2 weeks, 1, 3, 6 and 12 months.Ethics and dissemination This study received approval from the Institutional Review Board of Beijing Friendship Hospital, Capital Medical University (2022-P2-336-02). All participants will provide informed consent prior to enrolment, and the study will be conducted in strict accordance with the Declaration of Helsinki. Study results will be disseminated via peer-reviewed publications and presentations at academic conferences.Trial registration number ClinicalTrials.gov (NCT06365229) and Chinese Clinical Trial Registry (ChiCTR2200066192).